3.1.3. Synthesis of orthorhombic sulfur by hydrogen sulide reaction with cobalt-doped lamellar vanadyl phosphate (Communications in Inorganic Synthesis, 2015)
Abstract: In the present work, cobalt-doped vanadyl phosphate is synthesized and use to prepare orthorhombic sulfur by reaction with hydrogen sulfide. The obtained X-ray florescence results for the cobalt doped matrix are as follows: 93.36 % V2O5; 6.56% P2O5 and 0,08% Co2O3. The maximum H2S adsorption capacity was measure as 44.3 mg of H2S per gram of matrix. The interlayer distance (as measured by X-ray diffraction data) in the cobalt-doped matrix is 0.52 nm. It is verified by SEM images that orthorhombic sulfur crystals are formed.